2019
DOI: 10.1002/ab.21818
|View full text |Cite
|
Sign up to set email alerts
|

Serious violent behavior and antisocial outcomes as consequences of exposure to ethnic‐political conflict and violence among Israeli and Palestinian youth

Abstract: We examine whether cumulative-past and concurrent exposure to ethnic-political violence among Israeli and Palestinian youth predict serious violent behavior and antisocial outcomes toward the in-group and the out-group. We collected four waves of data from 162 Israeli Jewish and 400 Palestinian youths (three age cohorts: 8, 11, and 14 years old) and their parents. The first three waves were consecutive annual assessments, and the fourth was conducted 4 years after the third wave, when the three age cohorts wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 56 publications
1
24
0
Order By: Relevance
“…First, with welldesigned true experiments, exposure to weapons alone has been shown to cause an increased propensity for the observer to behave aggressively in the short run, albeit without weapons (Berkowitz & LePage, 1967; see also Anderson, Benjamin, & Bartholow, 1998;Ariel et al, 2019). Second, there are a number of well-done empirical studies that have shown that a youth's exposure to violence in any of multiple domains increases the risk for concurrent and later violent behavior by that youth, sometimes with weapons (Boxer et al, 2013;Dubow, et al, 2019). For example, youth exposed to ethno-political violence are more likely to behave aggressively against their peers (Ibid); exposure to family violence increases the risk of violence in children from that family (e.g., Boxer, Gullan, et al, 2009;Dodge et al, 1990); having violent peers increases the risk of a youth behaving violently (e.g., Espelage et al, 2003;Tolan, Gorman-Smith, & Henry, 2003); having violence in the neighborhood increases the risk of youth growing up in that neighborhood behaving violently concurrently and later (Guerra et al, 2003;Schwartz & Proctor, 2000); and exposure to various forms of media violence increases the likelihood of youth behaving violently later in life (sometimes with weapons; Anderson et al, 2007;Eron et al, 1972;Huesmann et al, 2003;Huesmann, 1986).…”
mentioning
confidence: 99%
“…First, with welldesigned true experiments, exposure to weapons alone has been shown to cause an increased propensity for the observer to behave aggressively in the short run, albeit without weapons (Berkowitz & LePage, 1967; see also Anderson, Benjamin, & Bartholow, 1998;Ariel et al, 2019). Second, there are a number of well-done empirical studies that have shown that a youth's exposure to violence in any of multiple domains increases the risk for concurrent and later violent behavior by that youth, sometimes with weapons (Boxer et al, 2013;Dubow, et al, 2019). For example, youth exposed to ethno-political violence are more likely to behave aggressively against their peers (Ibid); exposure to family violence increases the risk of violence in children from that family (e.g., Boxer, Gullan, et al, 2009;Dodge et al, 1990); having violent peers increases the risk of a youth behaving violently (e.g., Espelage et al, 2003;Tolan, Gorman-Smith, & Henry, 2003); having violence in the neighborhood increases the risk of youth growing up in that neighborhood behaving violently concurrently and later (Guerra et al, 2003;Schwartz & Proctor, 2000); and exposure to various forms of media violence increases the likelihood of youth behaving violently later in life (sometimes with weapons; Anderson et al, 2007;Eron et al, 1972;Huesmann et al, 2003;Huesmann, 1986).…”
mentioning
confidence: 99%
“…Protective factors for children confronted by social unrest and violence in society include self-control, adherence to the law and acceptance of police legitimacy (Lösel et al, 2018). Families are likely the greatest protective factor for young children (Dubow et al, 2019; Mathews et al, 2016) but as protests continue around the world in 2021, parents may be unaware of how much children see and hear, and how affected they are by events taking place in their environment. Further, our data show that family members were also negatively impacted by the protests and consequently these protective factors may not be operating effectively for young children.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show the impact of early traumatic experiences on the development of self-regulation which in turn influences attention, concentration and social interactions – all of which affect children’s ability to benefit from school education and to form positive relationships (Dawes, 2015). There is a plethora of evidence of the negative effects of war and political violence on children such as heightened aggression and violence (Dawes et al, 1989; Dubow et al, 2019; Huesmann et al, 2017; Liddell et al, 1994; Qouta et al, 2008), nightmares (Dawes et al, 1989; Liddell et al, 1994), regressive behaviour and anxiety (Dawes et al, 1989), emotional and behavioural problems and non-specific psychopathology (Mousa Thabet et al, 2006), post-traumatic stress (Punamäki et al, 2001), depression and poor school performance (Dawes et al, 1989; Liddell et al, 1994).…”
Section: Psychosocial Effects Of Violence On Young Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…Scientists were confident that that type of conflict could be resolved by answering the following questions. What were the reasons for the hostility of people during public Dubow et al, 2019). Researchers found that physical aggression, participation in youth demonstrations were closely related to the constant impact of ethnic and political violence in the past.…”
mentioning
confidence: 99%